Synthesis and Antimicrobial Study of Some New Chlorosubstituted Isoxazolines - Maurya, M.R.; Parhate, V.V.; Deshmukh, M.S.; Rajput, P.R. (Asian Journal of Chemistry, 2010)
Chlorosubstituted chalcones (1a-d) were allowed to react with hydroxylamine hydrochloride in DMF containing a little piperidine to give isoxazoline in 1.5 h and yields were found to be 75-80%. These compounds show antibacterial activity when assayed against some common human pathogens.